Phonetical and lexical peculiarities of Scottish English - Присяжнюк, О.Я. (Культура народов Причерноморья, 2007)
The aim of this article is to reveal the phonetical and lexical peculiarities of the
English language in Scotland. The author pays key attention to the fact that Scottish
English has its own normalized literary form and a rich literary heritage which permit
it to be regarded as a generally acceptable variant of the English language alongside
southern educated English or Standard British English, and such other widely recognized
variants as American English and Australian English. Целью этой статьи является рассмотрение фонетических и лексических
особенностей шотландского английского. Автор обращает внимание на тот
факт, что шотландский английский имеет свою собственную нормализированную литературную форму и такое богатое литературное наследие, что предоставляет право считать его всеобще признанной разновидностью английского
языка, наравне с южным вариантом либо стандартным английским и такими
другими широко признанными вариантами как американский и австралийский
английский. Метою цієї статті є розгляд фонетичних та лексичних особливостей шотландського англійського. Автор звертає увагу на той факт, що шотландський
англійський має свою нормалізовану літературну форму і таку багату
літературну спадщину, що дає можливість рахувати його як загально признаний
різновид англійської мови поряд з південним варіантом чи стандартним
англійським, а також іншими широко визнаними варіантами як американський
та австралійський англійський.